How to feed a dictator : Saddam Hussein, Idi Amin, Enver Hoxha, Fidel Castro, and Pol Pot through the eyes of their cooks - Szabłowski, Witold, 1980- (Penguin Books, an imprint of Penguin Random House LLC, 2020)
"Traveling across four continents, from the ruins of Iraq to the savannahs of Kenya, Witold Szabłowski tracked down the personal chefs of five dictators known for the oppression and massacre of their own citizens: Iraq's Saddam Hussein, Uganda's Idi Amin, Albania's Enver Hoxha, Cuba's Fidel Castro, and Cambodia's Pol Pot-and listened to their stories over sweet-and-sour soup, goat-meat pilaf, bottles of rum, and games of gin rummy. Dishy, deliciously readable, and dead serious, How to Feed a Dictator provides a knife's-edge view of what it was like to be behind the scenes at some of the turning points of the last century"--